An integrative approach to transitions in east central Europe - Šimral, Vít, 1986- (2007)
This study presents an attempt of synthesis of structuralism and actor-orientated approach, combining methods of the game-theory and structural determinism, in an analysis of transitions in Eastern Europe in the late 1980s. Such a combination promises to get over the rigid conditions of socio-historical macro-structures as well as the vague, non-explaining flexibility of games in political arenas. This study offers a tool for understanding how structural variables affect the possibilities of politicians and citizens during the process of democratic transition. Firstly, the existing development of both structuralist and rational-choice models for study of regime change is presented, together with a description of their major advantages and disadvantages. Secondly, techniques and models especially appropriate for research on Eastern European transitions are examined thoroughly, specifically concerning the particularities of transitions from post-totalitarian rule. This chapter is constructed upon the rational-choice theory’s assumptions and forms a theoretical framework for later sections of the study.